Manajemen Pendidikan Karakter: Kajian Semantik dan Implementasi Pembelajaran Dalam Surat Al-Luqman Ayat 12-19 - Muhammad Maulana; Marfu'ah Marfu'ah (Management of Education: Jurnal Manajemen Pendidikan Islam, 2024)
The purpose of this study was to examine the character education management based on the semantic study of Al-Qur'an surah Al-Luqman ayat 12-19 and its application to learning in SDN-SN Pengambangan 5 Kota Banjarmasin's fourth grade. This research used descriptive qualitative research methods. The primary data sources of this research were Al-Luqman ayat 12-19 Surah Al-Qur'an, headmaster, teacher of religious and moral education (PABP), and two fourth grade teachers of SDN-SN Pengambangan 5 Kota Banjarmasin, whereas relevant research results and documentation served as secondary data sources. Interviews, documentation, and content analysis methods were used to collect data. Data reduction, data display, drawing conclusions, and verification were all methods of data analysis. The findings of this research: 1) QS. Al-Luqman ayat 12-19 contain the meaning of Aqidah education, Worship Education, and Moral Education in the Family. 2) Implementation QS. Al-Luqman ayat 12–19 in learning in class IV at SDN-SN Pengambangan 5 Banjarmasin City cultivates religious values, discipline, responsibility, honesty, environmental love, and manners. 3) Management of character education is carried out in the form of planning, implementation and evaluation.